Financiamento do Sistema Único de Saúde: Análise do impacto financeiro de propostas legislativas para aumentar os recursos federais alocados ao sistema - Sérgio F. Piola (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Ensuring sufficient resources for the Unified Health System (SUS) has been a concern since its inception. The linking of resources from the Social Security Budget (OSS) provided for in the Transitional Provisions Act (ADCT) of the Federal Constitution of 1988 was not complied with, nor were the first Budget Guidelines Law (LDO) able to maintain a regular contribution of resources that the new system required. The approval of Constitutional Amendment (CA) 29 of 2000 brought the states, the Federal District and municipalities to the more regular financing of the SUS, but did not guarantee the necessary increase in federal resources, although it contributed to its stability, even if at an insufficient level. The failure of this attempt to increase the federal contribution to the SUS led to the intensification of the legislative production of proposals, of a very varied nature, to help solve the insufficiency of the federal contribution to the system. In this text, we seek to rescue the path of the main groups propositions that were processed by the Federal Chamber from 2003 to 2020 and made estimates of the financial impact of typical proposals of each group if they had been approved, comparing the estimated results of these proposals with the federal expenditure executed in the period with public health actions and services (ASPS). The study shows that there was no shortage of proposals from the Legislative in order to increase federal participation in the financing of SUS. It is observed that a greater stability in financing, provided by CA 29 of 2000, was fundamental for public health services not to suffer a solution of continuity, but that an additional political effort is needed to support the SUS so that this system increases its effective coverage, reduces inequalities of access and can effectively face future difficulties arising from epidemiological, demographic and technological factors that will put even more pressure on health spending and so that Brazil can get out of the uncomfortable position of being one of the few countries that, even having a system with the obligation to provide universal and comprehensive care, has a public spending on health much lower than private spending.
Keywords: H51; 330; healthcare financing; public funding of health care; Unified Health System